Training course in applied econometric analysis for young economists/researchers in Uzbekistan: December 2024 - International Strategic Center for Agri-Food Development (International Strategic Center for Agri-Food Development, 2024)
The stakeholder consultations organized by the CGIAR Initiative on Fragility to Resilience in Central and West Asia and North Africa (F2R-CWANA) in Uzbekistan1 demonstrated a significant need in Uzbekistan for training in quantitative policy analysis and research, including applied data analysis. IFPRI organized introductory and intermediate level training courses in applied quantitative methods and data analysis in collaboration with the Westminster International University in Tashkent (WIUT) from January 30 to February 3, 2023, and December 11-15, 2023, respectively. These courses received positive feedback from local stakeholders, including policymakers, universities, research institutes, and individual researchers. To meet the growing demand and interest in applied econometric analysis and policy research in the country, IFPRI, in collaboration with ICARDA, the International Scientific Center for AgriFood Development (ISCAD) under the Ministry of Agriculture and WIUT, organized a training course in applied econometric analysis from December 10-20, 2024. The following sections of the report provide detailed information about the course.